Principles of administrative Law - Jain, M. P. (Bombay, 1971)
The growth of administrative process in India may be said to have gathered momentum after Independence in 1947, or more particularly, after the inauguration of the Constitution of India in 1950 conferring a broad writ jurisdiction on the Supreme Court and the High Courts. The study of the Administrative Law in India, the concomitant of the administrative process, came on the horizon in 1957 when the Indian Law Institute held its first seminar on Administrative Law at New Delhi. The study of the subject received a further impetus in 1959 when the Indian Law Institute invited several leading law teachers of India for participating in a seminar on the Indian Administrative Law at Bangalore. Since then, gradually, the subject has caught the imagination of the students and teachers of law in India so that at present there is hardly any law school where the subject is not taught as a part of the LL.B. and LL.M. curricula either on a compulsory or on an optional basis.
Keywords: Administrative law